A randomized pilot trial of topiramate for alcohol use disorder in veterans with traumatic brain injury: Effects on alcohol use, cognition, and post-concussive symptoms. (1st September 2020) - Pennington, David L.; Bielenberg, Jennifer; Lasher, Brooke; Herbst, Ellen; Abrams, Gary; Novakovic-Agopian, Tatjana; Batki, Steven L.
Highlights: The first study of topiramate effects on alcohol use, mTBI symptoms, and cognition. Topiramate was not superior to placebo in reducing alcohol use in ITT analyses. Nor was it superior to placebo in reducing symptoms associated with mTBI. Topiramate reduced alcohol use at twice the rate of placebo in per-protocol analyses. Negative cognitive effects of topiramate resolved with taper. Abstract: Background: Topiramate is an effective treatment for alcohol use disorder (AUD) and has also been used in the care of mild traumatic brain injury (mTBI). This pilot study aimed to obtain a preliminary assessment of topiramate's efficacy in reducing alcohol use and post-concussive symptoms, and its potential negative impact on cognitive function in 32 Veterans with co-occurring AUD and mTBI. Methods: This was a prospective 12-week, randomized, double-blind, placebo-controlled pilot study of flexible-dose topiramate or placebo. Primary outcome was reduction of drinking days per week within the topiramate arm. Secondary outcomes included between group comparisons of alcohol use and craving, post-concussive symptoms, and cognitive function. Results: Drinking days per week significantly decreased within both the topiramate and placebo arm. There were no significant treatment-by-week interactions on alcohol use/craving, or post-concussive symptoms in intent-to-treat analyses. In per-protocol analyses, topiramate significantly reduced number of drinks per week compared with placebo. Topiramate transiently impaired verbal fluency and working memory. Processing speed, cognitive inhibition, and mental flexibility significantly improved between weeks 1 and 12, regardless of treatment arm. Conclusions: Significant improvement occurred in both the topiramate and placebo groups over 12 weeks of treatment in alcohol use and post-concussive symptoms. Among treatment completers there was greater reduction of alcohol use in the topiramate arm. Topiramate was also associated with negative but transient effects on cognitive function. Results suggest both a possible benefit for topiramate treatment in reducing alcohol use and some potential for negative cognitive effects in Veterans with AUD and mTBI.